A wideband MIMO antenna with high isolation for 5G application. Issue 3 (14th December 2021) - Zhou, Ziyan; Liu, Shaobin; Li, Wei; An, Tong; Hu, Zhiyong
Abstract: This letter presents a design of four‐element wideband multiple‐input‐multiple‐output (MIMO) antenna with improved isolation that covering 1.9–5.2 GHz for 5G application. The basic structure of the proposed MIMO antenna is meandering monopole; a dual‐band is generated by involving meandering L‐shape strip and inverted‐F strip, then coupling with a parasitic strip to generate wideband. By etching two H‐shape slots and two split‐ring resonator slots at the ground can enhance the isolation between two adjacent input ports. Antenna elements are rotated symmetrically and vertically distributed around the dielectric plate, the overall dimension of the MIMO array is 54 mm × 120 mm × 13 mm. Reasonable layout can reduce the user's influence on the antenna performance, so that each antenna element can work normally. The prototype is simulated, fabricated and measured. A good impedance matching (return loss <− 10 dB), high isolation (<−16 dB), high total efficiency (>65%), and low envelope correlation coefficient (ECC < 0.05) were obtained across the operation bandwidth, the gain of the antenna is 6.1 dB at 3.6 GHz. Through measurement, it is found that the results are basically consistent with the simulation results, indicating that both wide bandwidth and high isolation are successfully achieved and can be well applied in 5G communication.